The Domestic Institutionalisation of Human Rights: An Introduction. Issue 3 (3rd July 2019) - Jensen, Steven LB; Lagoutte, Stéphanie; Lorion, Sébastien
ABSTRACT: This article aims to explore recent developments in the 'domestic institutionalisation' of human rights. We argue that the trend towards 'domestic institutionalisation' has inspired renewed attention to the importance of national-level institutions within the international human rights regime, including revisiting the roles of state actors. These developments represent a response to bridging the implementation gap between human rights commitments and reality. The article captures a number of the constitutive elements and key points of debate that merit the focus on 'domestic institutionalisation' of human rights. As a substantive introduction to a Special Issue, the article also purports to further develop a research agenda focused on building strong and sustainable state institutions that protect and promote human rights and contribute to social change. More practically, this research agenda can also inform the strategical priorities of international organisations and international donors working with human rights implementation and capacity development of state actors in context.